EFEKTIVITAS TEKNIK MNEMONIK UNTUK MENINGKATKAN HASIL BELAJAR IPS MATERI PERJUANGAN MEMPERTAHANKAN KEMERDEKAAN - Herawati, Reni; Mashar, Riana; Pritama, Muhammad Atik (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2015)
This research aims to determine the effectiveness of the use of mnemonic techniques to improve learning outcomes social science in fifth grade of Elementary School. Design of this research is collaborative classroom actions research that researcher make collaboration with the teachers. This research is conducted to fifth grade students of SD Negeri Adikarto 2 Muntilan by 20 students. Technique of data retrieval is using the evaluation sheet instruments in the form of a written test. The variable in this study is a mnemonic technique as independent variables and the learning outcomes as the dependent variable. The results of student learning indicators showed that the  increasing  have to reach more than 75% to. This research was conducted in two cycles, each cycle included  two meetings.The results of the research show that the mnemonic technique can improve the student learning outcomes. The average value of the students learning in social science lesson before get the action (in prior action) is 60.25 whereas the result after the first action (first cycle) the results obtained 70.75 and in the second cycle the result is 79.75. The difference in the average value of the first cycle and the second cycle is 8.5. The percentage of completeness in the first cycle is 70% while the percentage of completeness in the second cycle up to 90%. It shows that there is the increased from phase I to phase cycle II. So, It can be concluded that the use of mnemonic techniques can improve the student learning outcomes in social studies learning.